Answer:
a.
![f(-1)=2](https://img.qammunity.org/2020/formulas/mathematics/college/j4rq7v4fwx4y6b1i6odn4ee9bwn07svsup.png)
b.
![f(3)=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/siztsi29vcqgylnzi4cmtx5a9q8m9nzpb7.png)
c.
![f(x-1)=x+2](https://img.qammunity.org/2020/formulas/mathematics/college/m7mpfwt8ry14vue2zg0fyr2h3zq3j80xos.png)
Explanation:
We are given that
![f(x)=x+1+2](https://img.qammunity.org/2020/formulas/mathematics/college/71ajo9y25md6yjpsvxojtc4k39k1631tzw.png)
a.We have to find the value of f(-1)
Substitute the value of x in the given function
Then, we get
![f(-1)=-1+1+2=2](https://img.qammunity.org/2020/formulas/mathematics/college/5g6quatl8lk7x2fqpgx0keoapayqjn0w1h.png)
![f(-1)=2](https://img.qammunity.org/2020/formulas/mathematics/college/j4rq7v4fwx4y6b1i6odn4ee9bwn07svsup.png)
b.We have to find the value of f(3)
Substitute x=3 then we get
![f(3)=3+1+2=6](https://img.qammunity.org/2020/formulas/mathematics/college/a233f12b49hekx3k6ids6slb7k31xgfcn0.png)
![f(3)=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/siztsi29vcqgylnzi4cmtx5a9q8m9nzpb7.png)
c.We have to find the value of f(x-1)
Replace x by x-1 then we get
![f(x-1)=x-1+1+2=x+2](https://img.qammunity.org/2020/formulas/mathematics/college/wedy1getrdjhl6q7uurgnql3ug04ngr6x7.png)
Hence,
![f(x-1)=x+2](https://img.qammunity.org/2020/formulas/mathematics/college/m7mpfwt8ry14vue2zg0fyr2h3zq3j80xos.png)